RESEARCH OF HONEY CONSUMERS BEHAVIOR IN PROVINCE VOJVODINA - Ćirić, Maja; Ignjatijević, Svetlana; Cvijanović, Drago (Economics of Agriculture, 2015)
The region of Vojvodina is considered to be very favorable for honey production, whereby the area of Fruska Gora is primarily considered as the most bountiful. However, one of the key problems that honey producers encounter is the lack of understanding of consumer behavior and therefore inability to create appropriate marketing strategies and programs. Therefore, the aim of this paper is to provide assistance to honey producers in Vojvodina, to lime honey producers from Fruska Gora with protected geographical origin in particular, to identify the motives, attitudes and buying habits of consumers of honey in Vojvodina. The conclusion is carried to summarize the obtained results about what type of honey consumers in Vojvodina buy, why, where, when, how often and what are their attitudes toward the introduction of a new brand of honey. Moreover, it presents the basic guidelines to honey producers for the improvement of marketing strategies and marketing programs.